2019
DOI: 10.1007/s13592-019-00647-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of corpora allata nucleus reveals insights into epigenetic mechanisms of caste differentiation in Melipona scutellaris stingless bees

Abstract: In most Hymenoptera, the caste differentiation is influenced by differential environmental cues (e.g., food), which affect larvae development. However, Melipona stingless bees represent an exception to this rule. Workers and queens can emerge from brood cells of the same size, with the same quantity and quality of food. The different phenotypes of female bees depend on the interaction of genetic and environmental components. This mechanism is driven by the juvenile hormone, a key physiological factor synthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
2
2
0
1
Order By: Relevance
“…Epigenetic modifications possibly represent an association between genotype and environment in the development of divergent phenotypes in Melipona females 48 . Our expression data of genes related to acetylation machinery reinforce previous findings of our group 48 , 49 that caste differentiation in M. scutellaris may be accomplished through an association of epigenetic mechanisms and endocrine signalling. Moreover, we showed that despite histone acetylation seems to be involved in M. scutellaris polyphenism, 10HDA alone is not able to promote queen differentiation in this stingless bee species.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Epigenetic modifications possibly represent an association between genotype and environment in the development of divergent phenotypes in Melipona females 48 . Our expression data of genes related to acetylation machinery reinforce previous findings of our group 48 , 49 that caste differentiation in M. scutellaris may be accomplished through an association of epigenetic mechanisms and endocrine signalling. Moreover, we showed that despite histone acetylation seems to be involved in M. scutellaris polyphenism, 10HDA alone is not able to promote queen differentiation in this stingless bee species.…”
Section: Discussionsupporting
confidence: 90%
“…We found that both the levels of phosphorylation at threonine 3 of histone H3 (H3T3-P) and the levels of monomethylation at lysine 4 of histone H3 (H3K4-Me) are higher in newly emerged queens than in workers at the same age 48 . Analysing corpora allata glands, which are responsible for JH production, we have shown that the territorial dispersion of heterochromatin could be an important epigenetic mechanism associated with the phenotypic plasticity in castes of this species 49 .…”
Section: Introductionmentioning
confidence: 98%
“…Melipona females [48] . Our expression data of genes related to acetylation machinery reenforce previous findings of our group [48,49] that caste differentiation in M. scutellaris may be accomplished through an association of epigenetic mechanisms and endocrine signalling. Moreover, we showed that despite histone acetylation seems to be involved in M. scutellaris polyphenism, 10HDA alone it is not able to promote queen differentiation in this stingless bee species.…”
Section: Epigenetic Modifications Possibly Represent An Association Bsupporting
confidence: 89%
“…We found that both the levels of phosphorylation at threonine 3 of histone H3 (H3T3-P) and the levels of monomethylation at lysine 4 of histone H3 (H3K4-Me) are higher in newly emerged queens than in workers at the same age [48] . Analysing corpora allata glands, which are responsible for JH production, we have shown that the territorial dispersion of heterochromatin can be an important epigenetic mechanism associated with the phenotypic plasticity in castes of this species [49] .…”
Section: Introductionmentioning
confidence: 99%
“…Em Camponotus floridanus, histonas desacetilases (HDACs) estão envolvidas na transição entre os comportamentos de forrageamento e guarda(SIMOLA et al, 2016) e as subcastas de operárias diferem em padrões de modificações de histonas em cerca de 18% do genoma(SIMOLA et al, 2013), sugerindo que estas funcional e modificações póstraducionais de histonas em Melipona scutellaris. Constataram que tanto os níveis de fosforilação da treonina 3 da histona H3 (H3T3P) quanto os níveis de monometilação da lisina 4 da histona H3 (H3K4Me) são maiores em rainhas recémemergidas do que em operárias na mesma faixa etária Schumann et al (2019),. em análise de corpora allata, mostraram que a dispersão territorial da heterocromatina é um mecanismo epigenético importante na plasticidade fenotípica das castas de abelhas sem ferrão Melipona scutellaris.…”
unclassified